Applying epidemic algorithm for financial service based on blockchain technology - Poonpakdee, Pasu; Koiwanit, Jarotwan; Yuangyai, Chumpol; Chatwiriya, Watchara (My University, 2018)
Our global market is emerging transformation strategy that can make the difference between success and failure. Smart contract systems through developments of technological innovations are increasingly seen as alternative technologies to impact transactional processes significantly. Blockchain is a smart contract protocol with trust offering the potential for creating new transaction platforms and thus shows a radical change of the current core value creation in third parties. These results in enormous cost and time savings and the reduced risk for the parties. This study proposed a method to improve the efficiency of distributed consensus in blockchains using epidemic algorithm. The results showed that epidemic protocols can distribute the information similar to blockchain.
Keywords: Blockchain; Distributed Consensus; Epidemic Algorithms; Financial Technology